2005
DOI: 10.1007/s00795-004-0259-y
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of histopathological and ultrastructural features of placental villi in pregnant Nepalese women

Abstract: The placenta is an important functional unit for gas transfer between mother and fetus. The placental membrane, consisting of trophoblast layer interposed between maternal and fetal blood, plays an active role for intensity of respiration, but no morphological evidence has been documented. Until now, it has been reported that fetal growth retardation and increased fetal mortality rate usually could be seen at high altitude. In an attempt to find the cause of high perinatal mortality rate in Nepal, this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 15 publications
2
27
0
Order By: Relevance
“…13 Villous hypervascularity may then be an adaptive change, as in pregnancy at high altitudes and fetal growth restriction. 5,18,19,39 Some authors conclude that vascular dilatation rather than proliferation is an adaptive change to chronic hypoxia. 32 The author regards this opinion as a moot point because even if villous capillaries are frequently congested in villous hypervascularity (Figure 1), their numbers of lumens are indeed increased as a result of branching angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Villous hypervascularity may then be an adaptive change, as in pregnancy at high altitudes and fetal growth restriction. 5,18,19,39 Some authors conclude that vascular dilatation rather than proliferation is an adaptive change to chronic hypoxia. 32 The author regards this opinion as a moot point because even if villous capillaries are frequently congested in villous hypervascularity (Figure 1), their numbers of lumens are indeed increased as a result of branching angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…7,8 It has been related to several chronic obstetric complications and outcomes, 4 to mention only perinatal deaths, maternal diabetes mellitus, chronic infection, in utero asphyxia, umbilical cord problems, congenital anomalies, fetal vascular thrombosis, maternal anemia, smoking, air pollution, and multiple pregnancy. 7,[9][10][11][12][13][14][15][16][17][18][19][20] The incidence of chorangiosis is low in the second trimester and increases in the third trimester, 21 in which it is lower in preterm than in term pregnancies. 22 Chorangiosis has statistically nonsignificantly clustered with preuterine hypoxia, multiple pregnancy, and normoblasts in fetal circulation.…”
mentioning
confidence: 99%
“…Many studies have supported the role of maternal hypoxia; pregnancy at high altitude was reported to be associated with maternal hypoxemic hypoxia with resultant intervillous blood hypoxia [47]. Also, it has been reported that chorangiosis is more common in higher altitude gestation placentas with an increasing number of capillary vessels [37,50]. Therefore, a chronic hypoxic stimulus may lead to villous hypervascularity and connective tissue proliferation, with a predominant increase in number rather than in size of capillaries, possibly in order to increase oxygen delivery to the fetus [37,47].…”
Section: Discussionmentioning
confidence: 98%
“…21,39 The pattern is evoked by maternal hypoxemia secondary to decreased oxygen pressure in the environment (pregnancies at high altitudes), decreased oxygen binding capacity of the maternal blood (maternal anemia), air pollution and maternal smoking, increased distension of the uterus (multiple pregnancy), and maternal diabetes mellitus (abnormal oxygen-hemoglobin dissociation curve). 21,[38][39][40][41][42][43][44] Clusters of multinucleate giant cells in the decidua basalis and excessive numbers of extravillous trophoblasts are less commonly seen in this than in other patterns of diffuse hypoxic placental injury, 21 most likely because of the association of PR with deep trophoblastic, myometrial invasion, which was proven, at least in maternal anemia. 45 This pattern has a better prognosis than other types of chronic hypoxic injury, 21 probably because of hypoxic preconditioning and resistance to ischemia-reperfusion injury during labor, as was proven in pregnancies at high altitudes 46 and multiple pregnancies.…”
Section: Patterns Of Chronic Hypoxic Placental Injurymentioning
confidence: 99%